Awareness and the Arguments for and against the International Classification of Functioning, Disability and Health among Representatives of Disability Organisations - Lundälv, Jörgen (Int J Environ Res Public Health, 2015)
Disability organisations have not been engaged in the debate about the International Classification of Functioning, Disability and Health (ICF) in Sweden. We wanted to know representatives’ attitudes about the ICF. The aim of the study was to elucidate the arguments for and against the ICF among representatives of disability organisations. The study consisted of eighteen representatives (from six disability organisations) that answered electronic questionnaires. The questionnaires involved ten open questions about the arguments for and against the ICF. The answers of the questionnaires have been categorized according to qualitative content analysis. Our results indicated four themes: awareness, arguments for and against, influence and the future. More than half of the representatives had very limited awareness of the ICF. There was an explicit criticism of individual classification but more positive comments about classification on an aggregated level. The most important issue for representatives was influencing social policy in society, not learning and spreading information about the ICF.